2008
DOI: 10.1364/oe.16.011193
|View full text |Cite
|
Sign up to set email alerts
|

Particle size-dependent giant nonlinear absorption in nanostructured Ni-Ti alloys

Abstract: The nonlinear absorption in nanostructured Ni-Ti alloys, fabricated by electrochemical deposition, was investigated at 532 and 1064 nm. The type of nonlinear absorption (saturable or reverse saturable absorption) was observed to depend on the laser intensity as well as on the nanoparticle size. The nanostructured Ni-Ti alloys comprising particle mean diameters of 20 and 30 nm exhibited large three-photon absorption (3PA coefficient approximately 10(6) cm(3)/GW(2)) and large two-photon absorption (2PA coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The size of the nanoparticles are not small enough to adversely affect the saturable absorption characteristics of the SA, leading to relatively typical SA behaviour. 47 This was also demonstrated by Molli et al , 48 who showed similar behaviour in vanadium pentoxide (V 2 O 5 ) nanoparticles.…”
Section: Fabrication and Characterization Of Nickel Oxide/chitosan Sa...supporting
confidence: 62%
“…The size of the nanoparticles are not small enough to adversely affect the saturable absorption characteristics of the SA, leading to relatively typical SA behaviour. 47 This was also demonstrated by Molli et al , 48 who showed similar behaviour in vanadium pentoxide (V 2 O 5 ) nanoparticles.…”
Section: Fabrication and Characterization Of Nickel Oxide/chitosan Sa...supporting
confidence: 62%
“…In recent years, development of materials with optimized nonlinear optical (NLO) properties has gained much impetus in applied and fundamental research owing to their potential uses in diverse disciplines including materials science, medicine, biophysics, chemical dynamics, atomic, molecular, solid-state physics, and surface interface sciences . The NLO materials are currently attracting considerable interest because of their large applications in telecommunication sector, optics, and optoelectronic devices. Many efforts have been made in the designing of different materials including polymer systems, natural and synthetic nanomaterials, organic and inorganic semiconductors, and molecular dyes that exhibit NLO responses. Among these NLO materials, metal free organic NLO materials are extensively explored owing to their optical modulation, optical switching, better signal processing, frequency shifting, and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The excited electrons are free carriers possessing a whole spectrum of energies, causing the ground state absorption band to bleach or reduce in intensity which results increase in transmission in open aperture z scan. Apart of the excited electrons pumped to higher energy levels, causing excited state absorption, RSA will be observed at higher influences [15].…”
Section: Resultsmentioning
confidence: 99%